2017
DOI: 10.1038/tp.2017.162
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-mediated NMDA receptor autoimmunity and cellular barrier dysfunction in schizophrenia

Abstract: Autoantibodies that bind the N-methyl-D-aspartate receptor (NMDAR) may underlie glutamate receptor hypofunction and related cognitive impairment found in schizophrenia. Exposure to neurotropic pathogens can foster an autoimmune-prone environment and drive systemic inflammation leading to endothelial barrier defects. In mouse model cohorts, we demonstrate that infection with the protozoan parasite, Toxoplasma gondii, caused sustained elevations of IgG class antibodies to the NMDAR in conjunction with compromise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 65 publications
0
42
0
Order By: Relevance
“…Antibodies were detectable in circulation by 2 weeks postinfection, increased gradually over the next 2 months, and remained high until the end of the experiment. In an earlier study (17), the time course of NMDAR antibody generation in mice with T. gondii type II infection showed a similar pattern.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Antibodies were detectable in circulation by 2 weeks postinfection, increased gradually over the next 2 months, and remained high until the end of the experiment. In an earlier study (17), the time course of NMDAR antibody generation in mice with T. gondii type II infection showed a similar pattern.…”
Section: Resultsmentioning
confidence: 52%
“…Emerging clinical observations suggest that infectious agents, such as herpesvirus, may trigger NMDAR autoantibodies (16). Interestingly, recent studies have reported that NMDAR autoantibodies are present in chronic murine toxoplasmosis (6,17). This raises the question of whether T. gondii is the origin of the autoantibodies.…”
mentioning
confidence: 99%
“…Exposure to Toxoplasma has been associated with increased blood-brain barrier permeability in SZ subjects (Kannan et al, 2017) and with substantial and widespread immune activation including increased C reactive protein (Tomasik et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine-induced GRA mediated GR dysfunction can explain a wide variety of disorders including autism (42), attention deficit hyperactivity (43,44), epilepsy (45,46), schizophrenia (47,48), autoimmune encephalitis (17,(49)(50)(51)(52), and psychosis (17,47,48,52,53).…”
Section: Neuropsychiatric Disordersmentioning
confidence: 99%